Changing a Medical Education Curriculum: Challenges of Change Communications - Cerimagi, Sabina (IJRDO - Journal of Business Management, 2018)
This paper investigates organisational change management in a curriculum change project at an Australian higher education institution and, more specifically, analyses the human factors in this process: communication strategies, empowerment and involvement, and overall approach to change management. As communication is the life blood of an organisation and the oxygen of change within any organisation, this paper emphasises communications strategies to engage and inform the relevant stakeholders in the change project. The study involves a specific case at the University of Sydney Medical School, where a change sizing survey was implemented. The findings reveal that for the change to be effective, stakeholders require involvement, empowerment and clear communications. This paper’s goal is to successfully implement change – an objective of which is stakeholder buy-in.